Of bastards, slaves, dogs and other things: discourses of bourgeois transgression and illegitimacy in two francophone sub-saharan novels - Kamara, Mohamed (Dalhousie French Studies, 2020)
The emergence and rise to preeminence of the bourgeoisie on the African political, social, and economic scenes have been the stuff of many novels. One could even argue that the rise of the sub-Saharan novel (because it is inherently connected to the colonial project) is more or less concurrent with the birth and rise of this class. In this essay, I seek to analyze the discourse of bourgeois transgression and illegitimacy as exemplified in two novels: Ahmadou Kourouma’s Les soleils des indépendances (1968) and Francis Bebey’s Le ministre et le griot (1992). The two works focus on the ruling elite in the immediate postcolonial period. In both novels, albeit in varying degrees, the colonial school is presented as the main catalyst of the change that occasioned the transgression decried by the members of the erstwhile aristocratic nobility.